The prognostic significance of tumour infiltrating lymphocytes in oral squamous cell carcinoma - Książek, Mariusz; Lewandowski, Bogumił; Brodowski, Robert; Pakla, Paweł; Kawalec-Książek, Marta; Fudali, Ludmiła; Ryś, Janusz (Polish Journal of Pathology, 2019)
Currently there is being conducted an extensive search to find new prognostic factors in oral squamous cell carcinoma which would assist in better patient management. One of the most promising prognostic markers is the density of tumour infiltrating lymphocytes. 100 cases of patients with oral squamous cell carcinoma that underwent surgical resection between 2006 and June 2016 at our institution were included in this study. From each case the most representative HE stained slide was identified and the density of tumour infiltrating lymphocytes were classified as non-brisk or brisk, which was included in the survival analysis. Upon analysis there was a strong correlation between non-brisk (n = 28) and brisk (n = 72) tumour infiltrating lymphocytes and the primary clinical outcomes: overall survival (p = 0.0472) and local recurrence-free survival (p = 0.00037). Univariate and multivariate Cox regression model confirmed the high prognostic value of tumour infiltrating lymphocytes as the independent prognostic indicator of better survival, being even superior, in our study, to the traditional pTNM system. This study provides robust evidence that the density of tumour infiltrating lymphocytes demonstrates a high prognostic significance in oral squamous cell carcinoma.